2020
DOI: 10.3390/biomedicines8040093
|View full text |Cite
|
Sign up to set email alerts
|

Comment in Response to “Temozolomide in Glioblastoma Therapy: Role of Apoptosis, Senescence and Autophagy etc. by B. Kaina”

Abstract: It is with great pleasure that we acknowledge the fact that our review on Temozolomide (TMZ) has initiated a discussion [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Results obtained with concentrations much higher than what can be achieved in patients may only be helpful to elucidate toxicities and off-target effects [23]. While it has frequently been suggested that a single high drug dose might be a good surrogate for repeated re-administration, we find this notion lacking in evidence [24]. Despite advances in in silico modelling, defining the clinically relevant and achievable concentration of a novel agent a priori remains virtually impossible [25].…”
Section: Theophrastus Bombast Von Hohenheimmentioning
confidence: 88%
“…Results obtained with concentrations much higher than what can be achieved in patients may only be helpful to elucidate toxicities and off-target effects [23]. While it has frequently been suggested that a single high drug dose might be a good surrogate for repeated re-administration, we find this notion lacking in evidence [24]. Despite advances in in silico modelling, defining the clinically relevant and achievable concentration of a novel agent a priori remains virtually impossible [25].…”
Section: Theophrastus Bombast Von Hohenheimmentioning
confidence: 88%
“…Autophagy and apoptosis were 2 important mechanisms and considered a new target for therapeutic interventions in brain tumors. 27 Therefore, searching key factors to regulate autophagy and apoptosis may be a vital step in the treatment of glioblastoma. However, the specific role of B4GalT1 for autophagy and apoptosis in glioblastoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is frequently described as a DNA alkylating prodrug that induces double-strand breaks of the DNA which eventually lead to apoptosis (Karachi et al, 2018;Sharifzad et al, 2019). Recently, a debate has emerged casting doubt on the precise molecular function of this component (Strobel et al, 2019;Kaina, 2019;Stepanenko and Chekhonin, 2019;Westhoff et al, 2020;Herbener et al, 2020). According to the traditionally proposed model, TMZ alkylates bases that are present in the DNA, leading to a mismatch during replication and induces futile rounds of DNA repair, finally ending in DNA strand breaks and apoptosis (Kaina, 2019).…”
Section: Introductionmentioning
confidence: 99%